2022
DOI: 10.1101/2022.03.14.483310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exogenous application of dsRNA for the control of viruses in cucurbits

Abstract: The recurrent emergence of virus diseases in intensive horticultural crops requires alternative control strategies. Topical application of dsRNA molecules homologous to pathogens has been proposed as a tool for plant virus control. These dsRNAs induce the silencing mechanism (RNAi) that degrades homologous dsRNAs. Cucumber green mottle mosaic virus (CGMMV) represents a serious threat to cucurbit crops. Since genetic resistance to the virus is not yet available in commercial varieties, we aimed to control this … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Hence, the more effective local and systemic silencing of GFP expression observed in 16c plants when siRNA is delivered as CD-nanocomposites [14] can be explained in terms of higher amount of siRNA available and the possible improvement of systemic movement of the coated RNAs, as results from our research. Although systemic GFP silencing has been so far observed only in N. benthamiana 16c plants [62], we and others have shown that virus-derived dsRNAs, or at least long RNA molecules, moves systemically in the plant, and result subjected to the RNAi machinery producing siRNAs and lead to symptom reduction after virus inoculation [16,18,63]. Thus, improving delivery methods for siRNA/dsRNA in foliar application will either decrease the amount of dsRNA needed or improve its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, the more effective local and systemic silencing of GFP expression observed in 16c plants when siRNA is delivered as CD-nanocomposites [14] can be explained in terms of higher amount of siRNA available and the possible improvement of systemic movement of the coated RNAs, as results from our research. Although systemic GFP silencing has been so far observed only in N. benthamiana 16c plants [62], we and others have shown that virus-derived dsRNAs, or at least long RNA molecules, moves systemically in the plant, and result subjected to the RNAi machinery producing siRNAs and lead to symptom reduction after virus inoculation [16,18,63]. Thus, improving delivery methods for siRNA/dsRNA in foliar application will either decrease the amount of dsRNA needed or improve its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Detection and quantitation by RT-qPCR of the small RNAs derived of the dsRNAs was performed as described previously (18). In this section we evaluated the siRNAs derived from the sprayed dsRNAs product of the RNAi machinery in the plant cell.…”
Section: Quantitation Of Sirnas In Proximal and Distal Parts Of The P...mentioning
confidence: 99%
See 3 more Smart Citations